If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 = 2x + 1 Reorder the terms: -2 + 8x = 2x + 1 Reorder the terms: -2 + 8x = 1 + 2x Solving -2 + 8x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 8x + -2x = 1 + 2x + -2x Combine like terms: 8x + -2x = 6x -2 + 6x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 6x = 1 + 0 -2 + 6x = 1 Add '2' to each side of the equation. -2 + 2 + 6x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 1 + 2 6x = 1 + 2 Combine like terms: 1 + 2 = 3 6x = 3 Divide each side by '6'. x = 0.5 Simplifying x = 0.5
| (x+4)(x+3)=0 | | 15-5(3-2x)=8x+3(x-5) | | 49q^2=9 | | (3x+1)(x+4)=0 | | 5n-3=3n-9 | | 7x-(-1)=2 | | 15(-42x+40)=15(-8+224) | | 6=-2(10x+7) | | x^2+2=-2 | | x^2+11=6x | | -9=-h/12+5 | | 7x-0=2 | | 2x+24+10=0 | | y=2x^2+16x-29 | | y=2x^2-16x-29 | | =27 | | 12x-3=40x+18 | | -2x=76+(-90) | | 3x^2-x+12=0 | | =7x(22) | | -4(4v-6)+2v=2(v+6) | | 76+(-90)=-14 | | 9-12p+5p=4+2 | | c-17=44 | | 180=(x+5)(x+8) | | 9x^2+9xy-2x-2y=0 | | 4x+7+3x=19x | | 15-6p+p-8= | | x-4y=c | | 1x+3=45 | | 7a+4=2 | | 0.06(x-.5)=0.06x+0.01 |